The Effect of Technology Perception and Learning Engagement on Student Satisfaction in Online Learning - Muh. Alwi; Risnashari Risnashari; Juhardi Juhardi; Kusmaladewi Kusmaladewi; Arifin Tahir; Sitti Wahidah Masnani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the effect of online learning engagement on student satisfaction, with time management as a mediating variable. Using a quantitative approach with a cross-sectional survey design, this study involved 150 students from the UPPBJ UT Makassar Program who were selected using cluster sampling techniques. The variables used in this study included online learning engagement, technology perception, and student satisfaction, which were measured using a 5-point Likert scale. The data were analyzed using Smart PLS version 4.0 software, which included measurement and structural model evaluation to examine convergent, discriminant, and reliability validity. The results showed that online learning engagement did not have a significant effect on student satisfaction, although there was a positive relationship. However, online learning engagement had a significant effect on technology perception, which in turn had a significant effect on student satisfaction. Technology perception played an important role as a mediator in the relationship between online learning engagement and student satisfaction, reinforcing the direct effect. This mediating effect shows that even though online learning engagement does not directly increase satisfaction, perceptions of online learning technology play a crucial role in increasing student satisfaction. This study provides insight into the importance of technology perceptions in online learning.